Description of six new species of Oecetis (Trichoptera, Leptoceridae) from Vietnam - Johanson, Jell Arne; Pham, Thai Hong; Malm, Tobias; Sjöberg, Tin (Zootaxa, 2020)
The following six new Oecetis species have been described and illustrated: O. lata, O. gretae, O. malickyi, O. porntipae, O. olahi, and O. hageni. The following three Oecetis species are recorded for the first time from Vietnam: O. maron Malicky & Chantaramongkol 2005 (in Malicky 2005), O. iakchos Malicky 2005, and O. jachin Malicky & Mey 2010 (in Malicky 2010a). We present new records of the following six Oecetis species that are previously known from Vietnam: O. raghava Schmid 1995, O. biramosa Martynov 1936, O. tripunctata (Fabricius 1793), O. meleagros Malicky & Thani 2005, O. asmada Malicky 1979, and O. empusa Malicky & Chaibu 2000. A map presents the distribution of the Oecetis species included in this report.